Consumerism of Food and Non-Food Products on Online Platforms - Luh Ayu Karunia Dewani; Ketut Budi Susrusa; Gede Mekse Korri Arisena; Ary Bakhtiar (Agribusiness Journal, 2025)
In the digital era, students increasingly rely on online platforms to fulfill their consumption needs for food and non-food products. The development of e-commerce and digital payment systems such as e-wallets has changed consumption patterns, offering ease of transactions and increasing the tendency of consumptive behavior. Consumerism, which is the tendency to buy excessively without considering actual needs, is a phenomenon that needs to be studied more deeply. Students are vulnerable to impulsive consumption due to promotions, discounts, and easy access to online products. This study examines the relationship between the use of e-wallets, e-commerce, and college students' consumerism levels in food and non-food shopping.